Biopsy-negative, varicella zoster virus (VZV)-positive giant cell arteritis, zoster, VZV encephalitis and ischemic optic neuropathy, all in one - Teodoro, Tiago (2014)
A 72-year-old man developed clinical features of giant cell arteritis (GCA) and ipsilateral ophthalmic-distribution zoster, followed within 2 weeks by VZV encephalitis and 2 months later by ischemic optic neuropathy. Temporal artery biopsy was histopathologically negative for GCA, but contained VZV antigen and VZV DNA in multiple non-contiguous (skip) areas. The collective clinical and laboratory findings revealed a remarkably close temporal association of zoster, multifocal VZV vasculopathy with temporal artery infection, biopsy-negative VZV-positive GCA and VZV encephalitis.